2003
DOI: 10.1248/cpb.51.990
|View full text |Cite
|
Sign up to set email alerts
|

Two New Bromotyrosine-Derived Metabolites from the Sponge Psammaplysilla purpurea

Abstract: Two new bromotyrosine-derived metabolites (1, 2) have been isolated along with the known compounds 3,5-dibromo-4-methoxyphenylacetonitrile, 3-bromo-4-methoxyphenylacetonitrile, 3-bromo-4-hydroxyphenylacetonitrile, 1-hydroxyuracil, 1-methoxyhemibastadin 2, purpuramine H and a steroid 5alpha,8alpha-epidioxycholest-6-en-3beta-ol from the sponge Psammaplysilla purpurea. Compounds 1 and 2 were characterized by interpretation of their spectral data. The antibacterial activity of these compounds is summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Marinoquinoline [22,23]; 3 . Dihydromonofarnesylacetone [27,28]; 4 . Pseudozoanthoxanthin-like compound (PZT) [24]; 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Marinoquinoline [22,23]; 3 . Dihydromonofarnesylacetone [27,28]; 4 . Pseudozoanthoxanthin-like compound (PZT) [24]; 5 .…”
Section: Resultsmentioning
confidence: 99%
“…Pseudozoanthoxanthin-like compound (PZT) [24]; 5 . Monooxofarnesylacetone [27,28]; 6 . Sargachromenol [27]; 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CH 2 Cl 2 : MeOH (1:1) extract of the freeze-dried sponge Psammalplysilla purpurea was subjected to gel filteration (Sephadex, LH-20, CH 2 Cl 2 : MeOH (1:1), followed by silica gel chromatography, eluting with step gradient of hexane-EtOAc mixtures to MeOH, to afford known compounds 3,5-dibromo-4-methoxyphenylacetonitrile, 3-bromo-4-methoxyphenylacetonitrile, 8 1-hydroxyuracil, 13 thymidine, 14 ergosterol, 15 purpuramine-L 2 7 C-NMR spectral data, the two-methyl signals at δ 2.76 and δ 3.60 were assigned to an ester methyl of a carbamate [δ 159.50 (s), 52.48 (q)] and to a methyl on nitrogen [δ 33.95 (q)], respectively. The structure of compound 1 was established by the study of heteronuclear multiple bond connectivity (HMBC) and nuclear overhause effect spectroscopy (NOESY) correlations.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] In continuation of our search for biologically active compounds from marine organisms [6][7][8] we have investigated the sponge Psammalplysilla purpurea Carter (Verongiidae), collected from Gulf of Mannar, at Mandapam coast during February 2003. A literature survey revealed that the genus Psammalplysilla has yielded several bromo tyrosine derive metabolites namely psammaplysillins, 9 purpuramines, 10 and macrocyclic bastadines.…”
Section: Introductionmentioning
confidence: 99%